In-situ polymerization of polyaniline in radiation functionalized polypropylene films. (12th June 2015) - Dispenza, Clelia; Sabatino, Maria Antonietta; Deghiedy, Noha; Casaletto, Maria Pia; Spadaro, Giuseppe; Piazza, Salvatore; Abd El-Rehim, Hassan A.
Abstract: In-situ generation of a nanodispersed conductive polymer within a polypropylene matrix has been pursued in order to obtain flexible, conductive films. Radiation grafting of acrylic acid to polypropylene (PP) has been applied to insert carboxyl functionalities on PP. The radiation-grafted films have been further derivatized with a variety of diamines and used as substrates for in-situ chemical oxidative polymerization of polyaniline (PANI). PANI grows as a thin skin from the surface of the film as well as an interpenetrated network in its interiors. Evidence of chemical attachment of PANI to PP has been sought by performing FTIR and XPS analyses after extraction of the unbound polymer. The influence of the nature of the substituent attached to PP on the optical and electrical properties of the films has been investigated. PANI-PP skin-core films have been also tested as flexible electrodes for further electrochemical growth of the conductive polymer. Graphical abstract: Highlights: Functionalization of polypropylene (PP) films by radiation grafting of acrylic acid. Interpenetration and chemical binding of polyaniline (PANI) by in-situ polymerization. Significant increase of conductivity for the flexible PANI/PP systems. Use of PANI/PP systems as flexible electrodes for PANI polymerization.